ECONOMIC INTELLIGENCE AND INTELLECTUAL CAPITAL IN AGRICULTURE COMPETITIVENESS - CASE STUDY - Nešković, Slobodan; Jovanović, Žaklina; Čavlin, Miroslav (Economics of Agriculture, 2016)
The process of globalization in the last few decades conditioned the many technological, economic and social changes which have transformed the world market of agricultural products and the impact on the competitive environment. In the modern world, creating material value in agricultural production more and more the result of the intangible factors and production is increasingly based on knowledge, skills and innovation of employees. In the industrial age the necessary resources to achieve competitive advantages were capital, natural resources and work, while in todays knowledge-based economy the importance is on the information, innovation, knowledge, intellectual capital and intellectual property - that have become the foundation of creating all other values. These values are, because of their great importance in achieving the modern competitive advantages, very often the target of economic intelligence and therefore require all available forms of protection. The sector of agricultural production can make a signifcant contribution to improving the overall national competitiveness if it is based on intellectual capital as evidenced by the country with highly developed agriculture. However, by observing global changes can be concluded that Serbia in this sector has unused potential for growth and development.